A study of the feeding characteristics of a small and medium-sized copepod species (Sinocalanus tenellus) using genetic analysis techniques: seasonal comparison of potential/eaten food sources focused on phytoplankton - Chae, Yeon-Ji; Oh, Hye-Ji; Kwak, Ihn-Sil; Chang, Kwang-Hyeon; Jo, Hyunbin (Frontiers in Marine Science, 2023)
In aquatic ecosystem, the food web structure based on composition and abundance of prey species influences the feeding characteristics of predators, resulting in changes to the structure and function of the entire food web. Zooplankton mainly feed on phytoplankton, but the method of analyzing the feed source through visual and microscopic identification of gut contents has limitations in applicable species and the low resolution of the analysis results. In this study, potential vs. eaten food sources of Sinocalanus tenellus, a small and medium-sized copepod species dominant in brackish waters, were analyzed based on phytoplankton operational taxonomic units detected from the habitat's raw water and treated whole bodies of S. tenellus. The alpha diversity and dominant/subdominant species of each potential and eaten food source were identified, and they were compared across seasons. At the same time, the feeding selectivity index (Ei) was calculated by identifying overlapping species in the potential vs. eaten food source pool. As a result, it was confirmed that not all surrounding potential food sources are fed on by S. tenellus, and that its diet can vary depending on the presence/absence of preferred prey. Metabarcoding techniques is considered to be an effective way to identify fluctuations in major food sources of zooplankton at the genus or species level. If uncertainties such as incomplete species identification as identified from the results of this study are improved through improving of analysis methods such as application of species-specific primers in the future, it will be useful for securing information on the feeding characteristics of small to medium-sized zooplankton.